Stress-eliminated liquid-phase fabrication of colloidal films above the critical crack thickness - Shiyuan Liu; Ying Hong; Wang Hong; Yi Zheng; Xiaodan Yang; Xuemu Li; Zhuomin Zhang; Xiaodong Yan; Yao Shan; Weikang Lin; Zehua Peng; Xingqi Zhang; et al. (Nature Communications)
Abstract The thickness of film materials is a critical factor influencing properties such as energy density, optical performance, and mechanical strength. However, the long-standing challenge of the intrinsic thermodynamic limit on maximum thickness often leads to detrimental cracking, compromising these desirable properties. In this study, we present an approach called the stress-eliminated liquid-phase fabrication (SELF) method. The SELF method eliminates the need for substrates to support the precursor solution used for film fabrication. We harness the intrinsic surface tension of the solution by confining it within specifically designed grids in a framework, forming suspended liquid bridges. This technique enables fabrication of crack-free ceramic films within a broad thickness range from 1 to 100 μm. Furthermore, the fabricated PZT films exhibit a high piezoelectric coefficient (d 33) of 229 pC N−1. The customizable grids not only offer design freedom for film topologies but also facilitate the fabrication of diverse film arrays without the need for destructive cutting processes. Moreover, the freestanding nature of these films enhances their adaptability for MEMS processing, and the “capillary bridge” topology allows the PZT films to be used in ultrasound focusing transmitter, providing possibilities in the medical imaging.